NR1H3 (LXRα) is associated with pro‐inflammatory macrophages, predicts survival and suggests potential therapeutic rationales in diffuse large b‐cell lymphoma. Issue 5 (9th August 2022) - Vegliante, Maria Carmela; Mazzara, Saveria; Zaccaria, Gian Maria; De Summa, Simona; Esposito, Flavia; Melle, Federica; Motta, Giovanna; Sapienza, Maria Rosaria; Opinto, Giuseppina; Volpe, Giacomo; Bucci, Antonella; Gargano, Grazia; et al.
Abstract: The role of macrophages (Mo) and their prognostic impact in diffuse large B‐cell lymphomas (DLBCL) remain controversial. By regulating the lipid metabolism, Liver‐X‐Receptors (LXRs) control Mo polarization/inflammatory response, and their pharmacological modulation is under clinical investigation to treat human cancers, including lymphomas. Herein, we surveyed the role of LXRs in DLBCL for prognostic purposes. Comparing bulk tumors with purified malignant and normal B‐cells, we found an intriguing association of NR1H3, encoding for the LXR‐α isoform, with the tumor microenvironment (TME). CIBERSORTx‐based purification on large DLBCL datasets revealed a high expression of the receptor transcript in M1‐like pro‐inflammatory Mo. By determining an expression cut‐off of NR1H3, we used digital measurement to validate its prognostic capacity on two large independent on‐trial and real‐world cohorts. Independently of classical prognosticators, NR1H3 high patients displayed longer survival compared with NR1H3 low cases and a high‐resolution Mo GEP dissection suggested a remarkable transcriptional divergence between subgroups. Overall, our findings indicate NR1H3 as a Mo‐related biomarker identifying patients at higher risk and prompt future preclinical studies investigating its mouldability for therapeutic purposes.